الإبتكار في الخدمة وأثره على الإحتفاظ بالزبون دراسة حالة متعامل الهاتف النقال أوریدو بالجزائر - حسان , بوزیان; مهدي , شباركة (Finance and Business Economies Review, 2018)
Using Hertog (2000) model of service innovation, this study aimed to highlight the impact of service innovation on customer retention as well as defining the nature of relationship between service innovation and customer retention in ooredoo telecomunication company in Algeria. descriptive approach was used in the theoretical part relying on the Arabic and foreign references specialized in the field of this study, and the field research methodology in the applied side of the study by distributing a questionnaire to the study sample. A total of 76 current users of ooredoo services participated in this study. Regression analysis was conducted to test the relationship between service innovation and customer retention. Results indicated that there is a statistical significance effect of service innovation on customer retention, lack of quick response to customer complaints by Ooredoo, the lack of using electronic systems as well as the modern equipment during the providing services to customers. Based on the results the following recommendations were given: Developing new systems to provide services to customers, responding to customer complaints very quickly and never neglecting it, in addition to using electronic systems when providing services to customers, which contributes to improving the efficiency of service providers.